LAIK your classroom: A practical framework to integrate generative AI in higher education classrooms (Journal of Applied Learning and Teaching, 2024)
The proliferation of generative artificial intelligence (GenAI) tools in the last two years and their ongoing development make their integration in education an inevitable reality. Recent studies into the integration of GenAI tools in academia have focused on opportunities for education and challenges to consider. In this context, few frameworks and models have been proposed, but none have addressed the need for a comprehensive and practical framework to facilitate teachers’ efforts to integrate GenAI into their classrooms. This study, therefore, addresses this research gap by developing a framework for the integration of GenAI in classrooms, the LAIK framework. The framework is designed to identify the necessary elements that should be considered before, during, and after integrating GenAI tools in higher education classrooms. To build the framework, data were collected from teachers, students, and classroom observations. Results from the study highlighted the need for four practical stages in this framework, namely (1) laying the foundation, (2) assembling GenAI-friendly classes, (3) investigating and monitoring, and (4) keeping the teacher informed. The framework also offers a variety of options to consider for practical ways to integrate GenAI technology to support learning in the classroom.